2022
DOI: 10.1371/journal.pone.0266051
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of recognition of intellectual disability for adults during hospital admissions: A retrospective data linkage study in NSW, Australia

Abstract: Adults with intellectual disability have high health care needs. Despite frequent contact with health services, they often receive inadequate health care. One method to improve health care delivery is reasonable adjustments, that is, the adaptation of health care delivery such that barriers to participation are removed for the person with disability. A starting point for the provision of reasonable adjustments is recognition of intellectual disability during the health care contact. To determine rates and pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Analysis of factors associated with unrecorded diagnosis showed that having a less severe intellectual disability was independently associated with increased likelihood of intellectual disability never being recorded in general hospital data, in keeping with previous research [ 37 ]. Mild intellectual disability may not be immediately obvious on meeting a person with the condition and specific enquiry may not be included in standard medical admission assessments.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Analysis of factors associated with unrecorded diagnosis showed that having a less severe intellectual disability was independently associated with increased likelihood of intellectual disability never being recorded in general hospital data, in keeping with previous research [ 37 ]. Mild intellectual disability may not be immediately obvious on meeting a person with the condition and specific enquiry may not be included in standard medical admission assessments.…”
Section: Discussionsupporting
confidence: 86%
“…There is no English benchmark against which the results of this study can be directly compared, although data suggest that low levels of recording of intellectual disability in healthcare records is an international issue. A recent study conducted in New South Wales, Australia, found an overall recognition of intellectual disability in only 23.79% of hospital admissions of adults with the condition and that recording had reduced over time [ 37 ]. A further Australian study that investigated the recording of intellectual disability in children showed that hospital data identified only 14% those with intellectual disability who had been admitted [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administrative authorization was also obtained from the District Health Service Buea, reference number F 1 Vol 2 /L/MINSANTE/RDPHSW/DHS/Buea/106a. Written formal permissions were obtained from heads of the ethics review committees of these health facilities in which they waived obtaining informed consent from patients to access data as has been done in other research works [12][13][14]. The data was collected anonymously and confidentiality was maintained by the non-identification of patients' information.…”
Section: Ethics Statementmentioning
confidence: 99%
“…For example, the 'Penrose hypothesis' was proposed in the UK to describe the increased number of people incarcerated following reductions in the number of psychiatry inpatient beds and has been used to illustrate how different parts of health care, social services and the criminal justice system are interconnected (Lamb, 2015;Wild et al, 2022). Policy documents from the US (Bronson et al, 2015;Concannon, 2019;Vallas, 2023), Australia (Rowe et al, 2017;Sharma, 2023) and the UK (Royal College of Psychiatrists, 2014;Warner, 2018;Williams & Braden, 2018) have highlighted concerns and called for changes in how care is provided to individuals with IDD both inside and outside of the system.…”
Section: Introductionmentioning
confidence: 99%